Precipitation modeling for prediction of the evolution of acoustic nonlinearity in an iron–copper alloy. (April 2022) - Fuchs, Brian; Kim, Jin-Yeon; Jacobs, Laurence J.
Abstract: Computational precipitation modeling tools are used to predict the nucleation and growth of copper precipitates in a Fe–1%Cu alloy isothermally aged at 500 °C up to 500 h. The size distribution is used to predict the classical material nonlinearity ( β ) of the alloy utilizing two existing physics-based models that relate the change in nonlinearity Δ β to the interaction of dislocations with coherency strains that develop around growing precipitates. The Δ β modeled qualitatively matches the increase in β observed experimentally. However, the precipitation model underpredicts precipitate radii measured in previous experimental work, resulting in an underprediction of Δ β.